Analisa Hirarki Klaster Perkotaan Di Wilayah Kabupaten Semarang - Abdullah, Abdullah; Priyoga, Iwan (Institut Teknologi Nasional Yogyakarta, 2023)
Semarang Regency comprises 19 sub-districts, each exhibiting varying levels of regional growth. In the year 2015, six sub-districts boasted a Gross Regional Domestic Product (GRDP) value exceeding one trillion rupiah. These notable sub-districts include Bawen District, East Ungaran District, West Ungaran District, Bergas District, Pringapus District, and Ambarawa District. Within these sub-districts lie urban areas that exert diverse degrees of influence. The primary objective of this research is to identify urban clusters that have formed within these five sub-districts under examination, shedding light on which urban areas wield the most significant influence. The research methodology employed is quantitative descriptive analysis. Secondary data collection involves the utilization of documentation techniques, encompassing the recording and analysis of statistical data closely aligned with the subject matter at hand. The findings of this study reveal that the urban clusters within Ambarawa District exert the most substantial influence, while those within Bawen District exhibit the least influence among the five sub-districts scrutinized. This study aspires to offer valuable insights to the Semarang Regency regional government, facilitating informed decision-making in designating Ambarawa as the focal point for urban development within the Semarang Regency area.